Traçados, cores e riscos: etnografia de uma cidade redesenhada pela pichação/graffiti - Dantas, Rodrigo Nathan Romanus (2018)
It is sought, in this research, the realization of an ethnography on pichação/graffiti in Santa Maria, a controversial and recurring theme in the local public debate. It is about understanding how visibilities/invisibilities of pichação/graffiti are constructed, the semantic struggles around the construction of the intelligibillity of the events about the pichação/graffiti in the city. As specific objectives we have: to trace the contours of regularities, the elements that give shape to the pichadores/graffiti artists as a group, their corporeities, reciprocities, values and motivations; to understand the logic of classification systems about the dichotomy between the terms “pichação” and “graffiti” in the local public debate; to understand conflicts and negotiations, intra and extra group, in these disputes of meanings around the pichação/graffiti in the city, carried out by the following social forces: pichadores/graffiti artists, State (public institutions), businesses/homeowners and newspapers/ intellectuals/ local artists; to reflect on the tensions and co-production of ethnographic gaze in the interaction between researcher and research interlocutors. In theoretical terms, this ethnography dialogues with authors as Clifford Geertz (1978), Néstor García Canclini (1997), Jacques Rancière (2005), Lévi-Strauss (2002), Eduardo Viveiros de Castro (2008), Gilberto Velho (1978) e José Magnani (2005). Methodologically, we use participant observation, close and prolonged interaction (2014 to 2017) between the pichadores/graffiti artists (24 individuals), which includes street interaction, cyberspace, and even housing sharing with one of them for six months. It was achieved, with this theoretical contribution and with the field work, glimpses of inversions, recombination, and semantic overflows of binary categories (legal/illegal, clean/dirty, right/wrong, light/shadow, beautiful/ugly, visible/invisible, downtown/periphery, etc.) of the universal act of classifying. With and against the pichadores/graffiti artists are the State (public institutions); the businesses/homeowners and the communicators/intellectuals/local artists. Each of these four social forces intends with the other, interacts in a logic of conflict and negotiation, has internal contradictions, two-way roads in these discordant encounters about the pichação/graffiti in the city. In and between each of these social forces there are different ways of constructing the intelligibillity of events, some based on certain dichotomies, in order to promote the criminalization of ilegal practice, while others build pichação/graffiti visibility/invisibility in the sense of problematizing the criminalization, to overflow, clutter and reorder binary classification systems, and/or promote the practice. From the point of view of the process of interpretation of these webs of meanings, of coproduction of the ethnographic, the pichação/graffiti ends up appearing as a sort of autobiographical narrative arc, an allegory demarcating inflections in the perception of the senses of living the city and in the life trajectory of the researcher himself.